Response of Bacterial Communities to Heavy Metal Contamination in an Abandoned Chromate Factory. Issue 5 (2nd May 2023) - Shan, Bing; Hao, Ruixia; Xu, Hui; Li, Jiani; Zhang, Junman; Li, Yinhuang; Ye, Yubo; Lu, Anhuai
Abstract: The chromium slags left by industry emission has caused serious damage to the local ecological environment, and microorganisms were sensitive to the variation in the surrounding environmental factors. In this work, 14 soil samples around an abandoned chromate factory were collected. We utilized the 16S rRNA regions from soil DNA to explore the possible effects of environmental factors on soil bacterial communities. High-throughput DNA sequencing results suggested that bacterial communities varied greatly from different soil samples, but Actinobacteria and Proteobacteria were predominant in all samples in the phylum level. In addition, Pseudarthrobacter, Thiobacillus, Paenisporosarcina, Sphingomonas, and Bacillus were abundant at a more refined species level. Based on redundancy analysis (RDA) and variation partitioning analysis (VPA), the results revealed that pH value, soil organic carbon (SOC), total nitrogen (TN), total phosphorus (TP), chromium (Cr) and lead (Pb) could obviously affect the bacterial community structure. Heavy metals, soil nutrients, and pH could explain 37.69%, 13.61%, and 31.41% of bacterial community variation, respectively. This study would provide a theoretical basis for future remediation of local Cr-contaminated soil.